2013
DOI: 10.1371/journal.ppat.1003539
|View full text |Cite
|
Sign up to set email alerts
|

SIGIRR, a Negative Regulator of TLR/IL-1R Signalling Promotes Microbiota Dependent Resistance to Colonization by Enteric Bacterial Pathogens

Abstract: Enteric bacterial pathogens such as enterohemorrhagic E. coli (EHEC) and Salmonella Typhimurium target the intestinal epithelial cells (IEC) lining the mammalian gastrointestinal tract. Despite expressing innate Toll-like receptors (TLRs), IEC are innately hypo-responsive to most bacterial products. This is thought to prevent maladaptive inflammatory responses against commensal bacteria, but it also limits antimicrobial responses by IEC to invading bacterial pathogens, potentially increasing host susceptibilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
75
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 49 publications
3
75
1
1
Order By: Relevance
“…In this study, we found evidence that IL-1R-dependent signaling plays a critical protective role during C. rodentium infection, in agreement with earlier studies (17,30). The most unusual finding in the present study was that infiltration of CD11b ϩ Ly6G ϩ Ly6C ϩ neutrophils, the main source of IL-22 secretion, was significantly delayed in the colon at an early time point during C. rodentium infection.…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we found evidence that IL-1R-dependent signaling plays a critical protective role during C. rodentium infection, in agreement with earlier studies (17,30). The most unusual finding in the present study was that infiltration of CD11b ϩ Ly6G ϩ Ly6C ϩ neutrophils, the main source of IL-22 secretion, was significantly delayed in the colon at an early time point during C. rodentium infection.…”
Section: Discussionsupporting
confidence: 93%
“…Many colonic pathogens, like enteropathogenic or enterohemorrhagic Escherichia coli (EPEC or EHEC, respectively), which are often modeled by murine challenge with Citrobacter rodentium, colonize the intestinal epithelium and can cause severe colitis along the epithelial barrier. 55,56 The colonic microbiota are known to influence susceptibility and resistance to these attaching and effacing pathogens, 57,58 since disrupting the mucosa-associated populations with antibiotics increased disease severity upon pathogen challenge. 59,60 Stressor induced shifts to luminal populations might also have downstream effects upon host metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel tissues fixed in 10% formalin, paraffin embedded, cut for histologic analysis, and stained with hematoxylin and eosin were subjected to pathologic scoring by 3 blinded observers (13,28).…”
Section: Methodsmentioning
confidence: 99%